2023
DOI: 10.1213/ane.0000000000006715
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pathophysiology of Delirium: An Overview of Biomarker Studies, Animal Models, and Tissue-Engineered Models

Tina B. McKay,
Zain Q. Khawaja,
Isaac G. Freedman
et al.

Abstract: Delirium is an acute brain disorder associated with disorganized thinking, difficulty focusing, and confusion that commonly follows major surgery, severe infection, and illness. Older patients are at high risk for developing delirium during hospitalization, which may contribute to increased morbidity, longer hospitalization, and increased risk of institutionalization following discharge. The pathophysiology underlying delirium remains poorly studied. This review delves into the findings from biomarker studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…Postoperative delirium is a common complication and is multifactorial in origin. 10 Ma et al 1 demonstrated a vasopressor-specific difference in the incidence of postoperative delirium, which is an important observation that deserves to be confirmed with an adequately powered randomized trial. Reduced cerebral blood flow as a mechanism leading to postoperative delirium seems plausible.…”
mentioning
confidence: 90%
“…Postoperative delirium is a common complication and is multifactorial in origin. 10 Ma et al 1 demonstrated a vasopressor-specific difference in the incidence of postoperative delirium, which is an important observation that deserves to be confirmed with an adequately powered randomized trial. Reduced cerebral blood flow as a mechanism leading to postoperative delirium seems plausible.…”
mentioning
confidence: 90%